Message-Driven Test Case Generation Framework - Demircioglu, Emine Dumlu; Kalipsiz, Oya (IEEE, 2020)
Testing can be conducted with either manually or automatically. It is very difficult to perform repetitive manual tests for functional correctness, especially in large-size business applications based on client-server architecture such as trading systems in stock exchanges and banking applications, because many different test scenarios are needed to test such systems. Conducting these test scenarios manually and on a human basis within a certain time is a time consuming, erroneous and tedious process. For this reason, end to end automation (test case generation, execution and error reporting) in repetitive manual tests will increase efficiency in software testing. In this context, an approach that generates automatically test scenarios for applications based on the client-server architecture communicating with each other using Application Programming Interface (API) messages is proposed in this study. In this paper, the message-driven test case generation framework is proposed for client-server architecture systems which are communicated with each other by using API messages. Basically proposed framework automatically generates test cases, which are extracted with reverse engineering mechanism from network packets between client-server communications over networks. The studying is motivated due to the fact that there is a lack of test automation framework in a specific domain: the system based on client-server architecture which uses API messages for the communication, such as financial applications, trading systems. Our approach will ensure the reuse of test scenarios, and will ensure 100% automation in the test process from the automatic generation of the test scenarios to the execution by future work.
Keywords: API Testing; Automation Test; Manual Test; TEST AUTOMATION; Computer Science